Percepção dos servidores técnico-adminstrativos dos centros de ensino da UFSM e UFMA quanto ao modelo de gestão de pessoas agency-community e os vínculos de comprometimento e entrincheiramento organizacional - Silva, Rogério Castro Destêrro e (2014)
This study aimed to compare the perception of the technical-administrative civil servants of UFSM and UFMA regarding people management agency-community model, and the binding types of commitment and organizational entrenchment. The research sample was 242 technical-administrative civil servants of UFSM and 139 of UFMA, with who was applied a questionnaire drawn from the assessment model of commitment and organizational entrenchment, proposed by Bastos et al. (2008), and people management agency-community model, proposed by Rousseau and Arthur (1999). Descriptive analyses were performed to investigate the accuracy of data entry, size and sample description, as well as variable distribution. Were identified high affective commitment to both institutions, high instrumental to UFMA and medium to UFSM, medium normative to UFMA and high to UFSM. The entrenchment has submitted an adjustment to the social position high to UFMA and medium to UFSM; medium alternative limitations to both institutions, and high impersonal bureaucratic arrangements to UFMA and medium to UFSM. Were identified high community models and medium agency models to both institutions. Were encountered, related to socio-demographic data, affective commitment, entrenchment and high community notion and medium agency notion between civil servants with over 46 years of both institutions; positive correlations when related the commitment dimensions, and entrenchment bases; positive correlations between people management community model and instrumental commitment in UFMA and affective in UFSM. Referring to agency model, the relationship, in UFMA, was negative, and, in UFSM, presented positive normative commitment correlations, entrenchment social position adjustment and alternative limitations. Regarding to entrenchment, the community model presented all correlation positive weak, in UFMA, and total relationship absence in UFSM. The agency model presented a negative correlation with entrenchment social position adjustment, in UFMA; in UFSM, presented positive relationship with the alternative limitations, social position adjustment and relationship absence with impersonal bureaucrats arrangement. The results show that the predominant civil servants bases is affective, followed by instrumental, once that the civil servants realize the existence of community practices in organizational people management actions. As a contribution, this study leave, in addition to comparative study, an extensive of published studies in the country and abroad and contributes to understanding the importance of adopting new people management models that consider the alignment between the individual and collective.